Factors that Influence the Intention to Purchase Halal Food Products (Case Study of Universitas Gadjah Mada Students) - Habibie, Haq Muhammad Hamka; Donna, Duddy Roesmara (Benefit: Jurnal Manajemen dan Bisnis, 2020)
Indonesia is a country that has the biggest Moslem population in the world. It causes an increase in demand for Islamic products, especially halal food products. The obligation to consume halal products become a huge market potential for food producers to produce halal products. This research aimed to find out the relation of factors that influence the intention to purchase halal food products.This research uses purposive sampling method with 200 respondents consisting of Muslim students from Universitas Gadjah Mada. Structural Equation Modelling was used to analyze existing data. This research uses halal awareness, product ingredients, Islamic brands, halal certification, product quality, and promotion as many factors that influence purchase intention of halal food products. Results showed that halal awareness, product ingredients, Islamic brands, halal certification, and product quality have a significantly positive effect on purchase intention of halal food products, but halal certification and promotion have no significant effect on purchase intention of halal food products.